Repositórios de dados de pesquisa em câncer: uma análise a partir do Re3data - Ramos, Jessica Fernanda dos Santos Lima (2021)
The relevance of health research data is gradually gaining prominence in the mainstream media. It is observed that the theme has been transcending the scientific and technological field, as it expands beyond the niche formed by scholars in the scientific field to which the data author and his team are part. Currently, it is through the reuse of research data stored in data management systems and located through management platforms that scientific and technological advances are obtained. In the field of health, the reuse of data has repercussions for the benefit of global public health. Bringing benefits in relation to the identification of diseases, in the development of treatments and vaccines and, also, in the improvement of medicines, transparency in public management and improvement in health policies. The present study aims to analyze the repositories of cancer research data registered in the Registry of Research Data Repositories (Re3data), in order to discuss the light of Information Science, how the cancer research data are represented in the data repositories research on a global scale. It is an exploratory and empirical study, where bibliographical and documentary researches were made on the subjects: health research data, oncology and research data management and access infrastructures, data repositories. The data analysis was qualitative, where the results obtained were analyzed with a view to: presenting the “state of the art” on cancer research data in an international context, identifying the specific repositories for storing cancer research data registered in Re3data and, finally, offering an overview as to the types of repositories, their subjects, nationalities, technologies and also as to the type of data involved in the storage of cancer research data in digital repositories.